PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP AUDIT REPORT LAG - Graffeliesta Widya, Maria; Hadiprajitno, Basuki (Diponegoro Journal of Accounting, 2013)
Financial report is one of stakeholder’s tools for making decision, therefore financial report are expected to have qualitative characteristics, which are relevant and reliable. To reduce the delay in submitting financial report, companies create good corporate governance mechanism. One of them is audit committee. The purpose of this study is to analyze the effect of audit committee characteristics to audit report lag. The populations in this study are all of non financial companies listed on the Stock Exchange in 2012. The sampling method used in this study was purposive sampling method. The total numbers of samples in this study were 228 research samples. Data about the audit committee information and audit report lag, are taken from the company’s annual report. Then, the data are analyzed using multiple regression linear analysis. The result of his research shows that from four characteristics of audit committee, the number of audit committee meetings and audit committee financial expertise has significant influence to reduce audit report lag. Meanwhile, the independence of audit committee and audit committee size has no effect to reduce audit report lag.